Review of community participation and FM services contributions toward provisioning of quality municipal services in Malaysian local authorities - Bello, Muhammad Umar; Martin, David; Kasim, Rozilah; Ahmad Aliyu, Aliyu (American Scientific Publishers, 2017)
Local authorities’ service delivery in recent times has categorised as a function of multiple players. Connecting with stakeholders such as customers, suppliers, employees, and local communities and their needs in an interactive session or communicative process has been classified as significant for successful Facilities Management (FM) services that bridges gaps that exist between those expectations and service provisioning that meets their wants and specific needs. FM will lead curtail wastage, less downtime and improve the bottom line. Beneficiaries of LAs services need to have a say in the decisions relating to the facilities provided, and if possible to take part in its provisioning or development and to manage it after completion. The methodology adopted in this research is secondary sources of data, were article, textbooks and statutory documents were critically reviewed. This study reviewed the community participation and FM services contributions towards enhancing and provisioning quality municipal services of LAs in Malaysia. This study shows that there are enormous benefits that both the LAs and local communities can achieve when community participation and FM services come together as a factor of service delivery. Service delivery changes have been complemented by improved community participation and FM systems. LAs in Malaysia can be successful in public sector service quality through the adoption of a community participation based on FM services approach. The results of this study shows that local government in Malaysia are yet to attain excellent level in times of community participation and FM service approach for adequate service delivery. A way forward lies on LAs to embrace service delivery best practice through synergy between community participation and FM at local levels, LAs should examine the revenue bases and expenditures of their local authorities, and the extent that their differences affect the capacity of local authorities in providing quality municipal services.